Interferon action: induction of specific proteins in mouse and human cells by homologous interferons. - Gupta, S L (1979)
Treatment of mouse (Ehrlich ascites tumor and L929) and human (FS4, GM258, etc.) cells with homologous interferons results in the induction of several proteins. Extracts obtained from cells labeled with [35S]methionine in the absence or presence of interferon were fractionated on poly(I) . poly(C)-agarose columns. The proteins retained on the columns revealed, upon sodium dodecyl sulfate/polyacrylamide gel electrophoresis, three protein bands in mouse cells (Mr 120,000; 80,000; and 67,000) and two in human cells (Mr 120,000 and 80,000) which were detected in the extracts of interferon-treated but not of untreated cells. These proteins were retained on double-stranded RNA [poly(I) . poly(C)-agarose] columns but very poorly, if at all, on single-stranded RNA [poly(I)- or poly(C)-agarose] columns, suggesting that they have an affinity for double-stranded RNA. In addition, interferon treatment of human fibroblasts greatly increased the labeling of three other protein bands (Mr 88,000; 67,000; and 56,000) which were detected in whole extracts but were not appreciably retained on poly(I) . poly(C)-agarose columns. The appearance of the induced proteins was blocked by actinomycin D if added together with interferon, indicating that transcription of certain genetic information is required. The possible correlation between the induced proteins described here and the elevated levels of certain enzymes in interferon-treated cells (a protein kinase and 2'-5'-oligoadenylate synthetase) is at present unclear.